NATIONALISM OF KH. HASYIM ASY'ARI IN AGUK IRAWAN MN'S NOVEL "PENAKLUK BADAI" (SOCIOLOGY OF LITERATURE): NASIONALISME KH. HASYIM ASY’ARI DALAM NOVEL “PENAKLUK BADAI” KARYA AGUK IRAWAN MN (SOSIOLOGI SASTRA) - Ria Agustina (Jurnal Kata, 2022)
The author was interested in analyzing this novel because it was very interesting and the storyline is related to our social life. It talked about a person lived during the colonial period and his struggle in achieving the independence through education. With education the spirit of nationalism and national awakening could be arised. It could be used as a guide for people lived in modern times. Education is very important, because through education people will have better understanding about their nation as well as a broad view about it. It would lead them to think about the future and independence of their nation. This study aimed to appreciate literary work by reading, studying, enjoying the story line and analyzing the novel. This study used a descriptive qualitative method, using a sociological study of literature. In the study of literature sociology, it discussed about 1). Religious value 2). Social community 3) Socio-cultural 4) and 5) Educational Value. The results of the research could be concluded that Aguk Irawan talked about nationalism based on historical documents of the Indonesian Independence day, which written in literary language. The biography novel of K.H. Hasyim Asy'ari Aguk Irawan described nationalism in form of an effort to expel the invaders, by providing nationalism education to the next generation, encouraging all elements of the nation, or expelling the invaders by lifting up the weapons.